2021
DOI: 10.3390/polym14010065
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Investigation of Polymer-Ceramic PCL/HA and PCL/β-TCP 3D Composite Scaffolds and Electrical Stimulation for Bone Regeneration

Abstract: Critical bone defects are a major clinical challenge in reconstructive bone surgery. Polycaprolactone (PCL) mixed with bioceramics, such as hydroxyapatite (HA) and tricalcium phosphate (TCP), create composite scaffolds with improved biological recognition and bioactivity. Electrical stimulation (ES) aims to compensate the compromised endogenous electrical signals and to stimulate cell proliferation and differentiation. We investigated the effects of composite scaffolds (PCL with HA; and PCL with β-TCP) and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 41 publications
1
14
0
Order By: Relevance
“…It is well know that osteogenic differentiation is regulated by multiple gene signaling pathways that lead to the upregulation of the transcriptional activity of RUNX-2. Furthermore, RUNX-2 can upregulate BMP2, an early marker of osteogenesis, and enhance the expression of late osteogenic differentiation genes (Ren et al 2022 ), which is considered an essential factor for the proliferation of osteoprogenitor cells during the differentiation of osteoblasts (Helaehil et al 2021 ). Several papers have speculated that osteoblasts and fibroblasts differentiated from mesenchymal stem cells are the major source of COL1 in various organs.…”
Section: Discussionmentioning
confidence: 99%
“…It is well know that osteogenic differentiation is regulated by multiple gene signaling pathways that lead to the upregulation of the transcriptional activity of RUNX-2. Furthermore, RUNX-2 can upregulate BMP2, an early marker of osteogenesis, and enhance the expression of late osteogenic differentiation genes (Ren et al 2022 ), which is considered an essential factor for the proliferation of osteoprogenitor cells during the differentiation of osteoblasts (Helaehil et al 2021 ). Several papers have speculated that osteoblasts and fibroblasts differentiated from mesenchymal stem cells are the major source of COL1 in various organs.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that E-beam did not alter the surface physical properties and cellular properties, but strengthened the mechanical and degradation properties, improved by 14% and 25%, respectively, which scaled up the suitability of PCL/β-TCP in bone restoration. Caetano et al 98 investigated the repair of DIW-PCL/HA implants through electrical stimulation (ES) in cranial defects in mice, and the implants significantly promoted the regeneration of bone White arrows showed the contact point of cells on the HA surface, which indicated that the cells were not completely spread on the HA surface. In contrast, cells were found completely spread on HA implant ornamented with dECM.…”
Section: Enhancing Cell Adhesionmentioning
confidence: 99%
“…Reproduced with permission from ref . Copyright 2017 Elsevier B.V. d) Cross-sectional images of bone tissue regeneration on implants determined by H&E. The image shows connective tissue (CT) and mineralized tissue (MT) . Reproduced with permission from ref .…”
Section: Future Perspectives For Additive Manufacturing Of Bioceramic...mentioning
confidence: 99%
“…The bone, a substantial organ comprising water, lipids, collagen, and hydroxyapatite (HA) [Ca 10 (PO 4 ) 6 (OH) 2 ], an inorganic phase, boasts extensive vascularization and remarkable mechanical strength. 1 Despite these attributes, bone faces challenges in self-regeneration, particularly in substantial defects resulting from infection, pathology, trauma, or congenital injuries. Autologous bone grafting, recognized as the gold standard, is employed due to its immunocompatibility, osteoconductivity, osteoinductivity characteristics, and angiogenic potential.…”
Section: Introductionmentioning
confidence: 99%
“…The critical-sized bone defect as the minimum area intraosseous lesion has no adequate vascularity and ability to repair itself with bone tissue. The bone, a substantial organ comprising water, lipids, collagen, and hydroxyapatite (HA) [Ca 10 (PO 4 ) 6 (OH) 2 ], an inorganic phase, boasts extensive vascularization and remarkable mechanical strength . Despite these attributes, bone faces challenges in self-regeneration, particularly in substantial defects resulting from infection, pathology, trauma, or congenital injuries.…”
Section: Introductionmentioning
confidence: 99%